Factors influencing inflation rate in Malaysia / Mohamad Azri Ibrahim - Ibrahim, Mohamad Azri (2022)
In economics, inflation is known as a rise in the general level of prices of goods and services in an economy over a period of time. When the price level increases, each unit of currency buys fewer goods and services. In short it can be said that inflation is a sustained rise in the general price level. The general price level is a price that reflects the overall price level for goods and services in an economy at a particular time. Inflation may cause many negative impacts on the economic growth of a country and the country itself. High inflation rate will increase the living cost and the living standards of people in a particular country. Over time, inflation became one of the most significant issues. It might be stated that during the last several years, Malaysia's inflation is caused by many factors. The aim of the paper is to determine factors that affect inflation in Malaysia. This paper consists of a quantitative method and the econometric model is used to identify the relationship between the dependent and independent variables. The dependent variable for this study is the inflation rate in Malaysia. Meanwhile, the independent variable for the study is Gross Domestic Product (GDP), Money Supply, unemployment rate, and Foreign Direct Investment (FDI). The main objective of this study is to determine whether or not macroeconomic variables will have a significant impact on the inflation rate in Malaysia. The time frame of the study is 1991 to 2020. Lastly, secondary information had been gathered to conduct the study.